2018
DOI: 10.1111/ijfs.13856
|View full text |Cite
|
Sign up to set email alerts
|

Neural network model for growth of Salmonella Typhimurium in brain heart infusion broth

Abstract: Summary Models that predict growth of Salmonella as a function of variables in the current and previous environment are valuable tools for assessing the safety of food. Therefore, this study was undertaken to develop a model for growth of Salmonella Typhimurium in brain heart infusion broth as a function of previous pH (5.7–8.6), temperature (15–40 °C), pH (5.2–7.4) and time. Viable count data (log CFU mL−1) were modelled using a neural network approach. The variable impacts were 2.4% for previous pH, 29.0% fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In addition, it was based on the convention used in Com-Base (Baranyi & Tamplin, 2004). Based on previous studies (Oscar, 2009(Oscar, , 2014(Oscar, , 2017a(Oscar, , 2017b(Oscar, , 2018a(Oscar, , 2018b(Oscar, , 2021, data were tagged for testing as follows: (a) for a time course of 30 days at 9 and 21 days; (b) for a time course of 14 days at 4, 9, and 13 days; and (c) for a time course of 3 days at 1 and 2.25 days. This resulted in 270 (82%) data for training and 58 (18%) data for testing the ANN during training.…”
Section: Data Source and Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it was based on the convention used in Com-Base (Baranyi & Tamplin, 2004). Based on previous studies (Oscar, 2009(Oscar, , 2014(Oscar, , 2017a(Oscar, , 2017b(Oscar, , 2018a(Oscar, , 2018b(Oscar, , 2021, data were tagged for testing as follows: (a) for a time course of 30 days at 9 and 21 days; (b) for a time course of 14 days at 4, 9, and 13 days; and (c) for a time course of 3 days at 1 and 2.25 days. This resulted in 270 (82%) data for training and 58 (18%) data for testing the ANN during training.…”
Section: Data Source and Descriptionmentioning
confidence: 99%
“…In the past, ANN was difficult to use in predictive microbiology applications. However, with the arrival of commercial software programs, it is now easy to develop ANN models for foodborne pathogens (Oscar, 2009(Oscar, , 2014(Oscar, , 2017a(Oscar, , 2017b(Oscar, , 2018a(Oscar, , 2018b(Oscar, , 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five microliters of a frozen (−80 C), thawed, and resuspended stock culture of Salmonella Newport was added to 0.7 ml of BPW in a 1.5 ml polystyrene, micro-centrifuge tube. Stationary phase cells, as determined by a predictive model (Oscar, 2018b), were obtained by incubating the culture for 96 hr at 22 C.…”
Section: Inoculation Culturementioning
confidence: 99%
“…Despite the fact that a large number of studies on the electroporation of cytomembrane have been reported (Saldaña et al ., ; Liu et al ., ), the mechanism of PEF treatment to inactivation micro‐organism is still not fully understood. In addition, when under external stress the cytomembrane makes alterations in its fatty acid composition, which affects many functions of the cell, especially membrane fluidity (Oscar, ; Niu et al ., ), there appears to be a relationship between membrane fluidity and bacterial resistance to environmental stresses (Niu et al ., ). In general, lower pH, greater heat and pressure resistance of bacteria are found in cells with a lower membrane fluidity (Cebrián et al ., ; Ou et al ., ), which might provide a new clue to explain the inactivation of micro‐organisms by PEF treatment.…”
Section: Introductionmentioning
confidence: 99%